Role of the Modern Libraries on Information and Communication Technology Era. - Dayananda, A.P.M.M.D.B. (Department of Library and Information Science, Faculty of Social Sciences, University of Kelaniya, Sri Lanka., 2017)
Information is very essential thing for human development as air is essential for the survival of all living organisms on earth, including human beings. At 21st century has ainformation exploration on the modern society. There for every person have to expose for the Information and Technology. The pace of change brought about by new information technologies has a key role on the way people live, work, and play worldwide. The increasing role played by information and communication technology in the development of library services for an active reaction to the challenges of the information service providing. The paper attempts to discuss the development of Information Technology, its application and also its effects in the library services. Today libraries are equipped to accomplish the newly Information Technology based services. Information are the kind of basic want in the modern society. Information Technology enabled services fulfill the information needs of the users at the right time in the right place to the right person.
Keywords: ICT; Libraries; Electronic Library; Digital Library; E-Resources